Insulin resistance in type 1 diabetes - เกียรติศิริโรจน์ , นพดล; พรอนุวงศ์ , รติกร; รอดอารีย์, เพชร (Journal of Health Science of Thailand, 2026)
During recent years, the condition whereby insulin resistance and type 1 diabetes combine, namely Double Diabetes, has become more widely recognised by scientific communities, in line with the increasing prevalence of obesity among populations with type 1 diabetes. Ample evidence shows that insulin resistance plays an important role in the increased risk of vascular complications, independent of glycaemic control. Given the increased prevalence of individuals with features of double diabetes, pragmatic diagnostic criteria are paramount. In this review, we discuss the potential role of estimated glucose disposal rate as an assessment of insulin resistance for individuals with type 1 diabetes. We also discuss the challenges of managing insulin resistance given that factors including peripheral insulin administration and fear of hypoglycaemic impede weight management in this group. Non-insulin therapy such as sodium-glucose cotransporter 2 inhibitors or glucagon-like peptide-1 receptor agonists may also have an additional role in improving insulin resistance but more studies on this topic are required before drawing any robust conclusion.